A new approach for modelling the fibre path in bolted joints of continuous fibre reinforced composites. (1st July 2020) - Roth, Sven; Pracisnore, Florian; Coutandin, Sven; Fleischer, Jürgen
Highlights: Bolted joints in continuous fibre reinforced structures. Fibre conform hole forming. Analytical fibre pathway description. Abstract: A fibre conform hole forming into continuous fibre reinforced components leads to beneficial part properties, as the fibre structure is not damaged in comparison to a drilling operation due to a reorientation of the fibres during the preforming process. To determine precisely the local component properties of the manufactured composite part, detailed information about the resulting fibre paths is required. For the first time, this paper provides a universal methodology to approximate the actual fibre paths in the reoriented area around the hole. Based on a few experimental data, the developed framework allows the construction of the fibre pathways depending on the formed hole diameter and the used fabric type. Two models based on polynomial splines are developed and compared with regards to the achievable model accuracy. The overall methodology is evaluated using different hole diameter and fabric types. Here, a very good correlation between approximation and reality is observed.